(untitled) (Research, Society and Development, 2025)
The present study aims to conduct a literature review on the association between physical activity and sedentary behavior in the health of older adults. This narrative review, drawing exclusively on systematic reviews retrieved from PubMed and BVS, synthesizes evidence on the links between physical activity, sedentary behavior, and older adults’ health. Consistent findings show that moderate-to-vigorous activity relates to higher quality of life, lower mortality, and better cardiometabolic, cognitive, and emotional outcomes. Prolonged sedentary time is associated with adverse body composition, increased cardiometabolic risk, and functional and cognitive decline. Common barriers include functional limitations, fear of falling, and psychosocial factors, whereas facilitators include social support and perceived benefits. Multicomponent interventions, including usable and tailored digital approaches, increase activity levels, though reductions in sedentary time remain modest. Integrated, context-sensitive strategies that balance 24-hour movement are therefore crucial.